Risk factors for drug hypersensitivity reactions in children - Francesca Mori; Francesca Saretta; Sara Riscassi; Silvia Caimmi; Paolo Bottau; Lucia Liotti; Fabrizio Franceschini; Annamaria Bianchi; Rocco Luigi Valluzzi; Giuseppe Crisafulli; Carlo Caffarelli (BMC, 2024)
Abstract Drug hypersensitivity reactions are common in children. Risk factors predisposing to IgE-mediated drug allergies and delayed drug reactions are a matter of debate. Gender, age, previous reactions to the same drug or to another drug, reduced drug metabolism, chronic diseases, polypharmacy, drug doses are linked with the onset of hypersensitivity reactions in some children. Novel advances in genetic polymorphisms can rapidly change the approach to the prevention of reactions since gene testing can be a useful screening test for severe cutaneous adverse reactions. Viral infections may act as cofactors in susceptible individuals. Polypharmacy, high doses, repeated doses and parental route of administration are also risk factors. Clinicians should take into account risk factors to allow the risk-benefit balance to be maintained.